Zinc in pregnancy, associated with prolonged labor - Sare Bakouei; Fatemeh Bakouei; Fatemeh Reisian; Azita Goshtasebi (Babol University of Medical Sciences, 2015)
Introduction: It is plausible that pregnancy may result in a decrease in the serum zinc concentration. The concentration of serum zinc is an important determinant of maternal complications. The aim of the current study was to identify serum zinc concentration and evaluate the possible correlation of this concentration with the length of first and second stage of labor in the pregnancy. Methods: In an observational prospective study, 432 pregnant women, 18 to 35 years of age, from urban primary health care centers in Tehran (Iran) were selected through a multi-stage sampling method and sampling proportionate to size. The blood samples were obtained for the measurement of maternal serum of iron and zinc in healthy singleton pregnancy between 14 to 20 weeks of gestational age, which was accomplished through electro-thermal atomic absorption spectrometry and zinc the standard procedure, respectively. Meanwhile, the length of the stages of labor was also recorded. Serum zinc and serum iron concentrations during early pregnancy, which are associated with prolonged labor, were also analyzed. Results: Maternal zinc and iron deficiency during pregnancy were found to be around 28.7% and 16.0%, respectively. The overall proportion of prolonged labor was 13.5%. The women with prolonged labor significantly had lower zinc concentration (p=0.03), However, there was no association between prolonged labor and zinc/ iron deficiency after adjusting for confounders. Conclusion: The findings of the current study indicated that a high prevalence of zinc deficiency was identified among the pregnant women in the second stage of pregnancy. Therefore, it is important to emphasize the need for further research for the evaluation of potential risk factors for maternal complications.